Study guides

☆☆

Q: -7m-3m plus 5m

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

15m + 4n - 5m + 9n = 10m + 13n

-5m-3+4 = 11 -5m = 11+3-4 -5m = 10 m = -2

5m - 5 + 2 = 1 Therefore, 5m - 3 = 1 5m = 4 m = 4/5 m = 0.8

5(m+/n

It can be simplified to: 9m-2n

Related questions

5m-5n+5m+5n When simplified: 10m

5m - 6 + m + 10 = 6m + 4

5m-3x+3m+2x 2m-x

It is simply: 5m+2

8m + 3n - 5m + 10n = 3m +13n

15m + 4n - 5m + 9n = 10m + 13n

3+4m+5m=214m+5m=21-39m=18m=18/9m=2

It is: 9m +8 -4m +7 -5m = 15

-5m-3+4 = 11 -5m = 11+3-4 -5m = 10 m = -2

-3m = 5m+8 -3m-5m = 8 -8m = 8 m = -1

5m+3=3m+9 5m+3-3=3m+9-3 5m=3m+6 5m-3m=3m+6-3m 2m=6 (2m)/2=6/2 m=3

-8 + (5m - 6m) = -8 + (-m) = -8 - m

People also asked